2018
DOI: 10.5152/tjar.2018.29577
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Passive Leg Raising, Stroke Volume Variation and Pulse Pressure Variation to Predict Fluid Responsiveness During Weaning From Mechanical Ventilation After Cardiac Surgery: A Prospective, Observational Study

Abstract: Objective: During assisted ventilation and spontaneous breathing, functional haemodynamic parameters, including stroke volume variation (SVV) and pulse pressure variation (PPV), are of limited value to predict fluid responsiveness, and the passive leg raising (PLR) manoeuvre has been advocated as a surrogate method. We aimed to study the predictive value of SVV, PPV and PLR for fluid responsiveness during weaning from mechanical ventilation after cardiac surgery. Methods: Haemodynamic variables and fluid respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
2
0
2
Order By: Relevance
“…However, patient's bedside conditions of measurement of these dynamic indices at ICU remain a still moot issue. Experimental studies have shown conflicting results regarding the accuracy of PPV to individually predict the response to volume expansion in patients mechanically ventilated under PC versus VC modes [1][2][3][4]. Moreover, most of the validation studies of PPV as fluid responsiveness predictor in critically ill patients have exclusively included patients who were ventilated with VC mode, generally with a tidal volume > 8 ml kg −1 of ideal body weight (IBW).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, patient's bedside conditions of measurement of these dynamic indices at ICU remain a still moot issue. Experimental studies have shown conflicting results regarding the accuracy of PPV to individually predict the response to volume expansion in patients mechanically ventilated under PC versus VC modes [1][2][3][4]. Moreover, most of the validation studies of PPV as fluid responsiveness predictor in critically ill patients have exclusively included patients who were ventilated with VC mode, generally with a tidal volume > 8 ml kg −1 of ideal body weight (IBW).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the expected effect of spontaneous breathing on variations in left ventricular SV may be inverted to the effect of mechanical ventilation (MV), due to inverted cardiopulmonary interactions. Moreover, respiratory changes in intra-thoracic pressure during pressure control mode might be insufficient to modify loading conditions of ventricles [3,13]. Therefore, the ability of PPV to predict fluid responsiveness in septic patients mechanically ventilated with pressure-controlled mode is still under debate [11].…”
Section: Introductionmentioning
confidence: 99%
“…Duas metanálises recentes demonstraram alta acurácia do teste em predizer o aumento do índice cardíaco (IC) na terapia intensiva 20,21 . Entretanto, os resultados dos poucos estudos realizados no pós-operatório de cirurgia cardíaca demostraram acurácia do teste inferior [22][23][24] e, portanto ainda faltam evidências nesta população.…”
Section: Imcunclassified
“…Diversos estudos realizados em cirurgia cardíaca, demostram a inabilidade da PVC com preditor da resposta ao fluido 22,69 , reportando AUC ROC entre 0,58 15 , 0,58 70 , 0,34 intraoperatório antes da cirurgia 71 A pressão positiva da ventilação mecânica provoca uma diminuição cíclica do volume sistólico do ventrículo direito por dois mecanismos:…”
Section: Sistemas De Análise Do Contorno De Pulso Não Calibradosunclassified